Safeguarding villagers’ access to foods from timber trees: Insights for policy from an inhabited logging concession in Gabon - Taedoumg, H.E.; Maukonen, P.; Mikolo Yobo, C.; Midoko Iponga, D.; Noutcheu, R.; Chupezi Tieguhong, J.; Snook, Laura K. (Elsevier, 2018)
This study assessed the abundance of and access to tree species (Ozigo, Dacryodes buettneri; and Abam, Gambeya lacourtiana) that yield edible fruits to villagers and timber to the logging industry in and around a logging concession in Gabon. Participatory mapping combining GPS coordinates and interviews was carried out with 5 female and 5 male collectors in each of two villages within or adjacent to the logging concession. Precommercial and harvestable (>70 cm dbh) Ozigo and Abam trees, as well as their stumps, were also quantified on 20 five ha plots in the 2012 cutting area of the concession and on 21 five ha plots on 10 km transects from each village. Distances to 59 Abam and 75 Ozigo from which fruits were collected ranged from 0.7 to 4.46 Km from the village centres. Most collections were by mixed groups made up of men, women and children (54%) at an average of 1.21 ± 0.09 km; or by men and women (18%) at 2.21 ± 0.15 km; or women and children (14%) at 4.03 ± 0.22 km from the village. Almost 28% of all of the collection trees were inside the logging concession boundaries but outside the village agricultural zone, 43% were inside the village agricultural zone, and 29% were outside the logging concession. Only 33% of Ozigo collection trees had reached commercial size while 75% of Abam trees had. No stumps were found on any sample plots, probably reflecting the ban on felling Ozigo which was in effect at the time; and the relatively low commercial value of Abam. Densities of precommercial Ozigo trees in the cutting area were more than double their densities around the villages (236.0 ± 20.3100 ha−1and 96.6 ± 17.2100 ha−1, respectively), while densities of harvestable Ozigo trees were 7 times higher in the cutting area than around villages (120 ± 20.2100 ha−1and 17.1 ± 3.4100 ha−1respectively). This probably reflects past and current anthropogenic pressures around the villages, including logging and land clearance for agricultural fields. Densities of precommercial Abam were almost four times higher around the village (22.3 ± 5.6 and 6.0 ± 2.9) than on the cutting area. Villagers did not record a decline in availability of or access to these fruits over the past 5 years, suggesting little or no immediate conflict between timber production and access to fruits from these trees.